:: Propositional Linear Time Temporal Logic with Initial Semantics
:: by Mariusz Giero
::
:: Received October 22, 2015
:: Copyright (c) 2015-2018 Association of Mizar Users
:: (Stowarzyszenie Uzytkownikow Mizara, Bialystok, Poland).
:: This code can be distributed under the GNU General Public Licence
:: version 3.0 or later, or the Creative Commons Attribution-ShareAlike
:: License version 3.0 or later, subject to the binding interpretation
:: detailed in file COPYING.interpretation.
:: See COPYING.GPL and COPYING.CC-BY-SA for the full text of these
:: licenses, or see http://www.gnu.org/licenses/gpl.html and
:: http://creativecommons.org/licenses/by-sa/3.0/.
environ
vocabularies FINSEQ_1, CARD_1, ORDINAL4, SUBSET_1, NUMBERS, ARYTM_3, TARSKI,
RELAT_1, XBOOLE_0, FUNCT_1, XBOOLEAN, MODELC_2, CQC_THE1, NAT_1,
XXREAL_0, ARYTM_1, PARTFUN1, MARGREL1, HILBERT2, ZFMISC_1, ZF_MODEL,
FINSET_1, RFINSEQ, LTLAXIO1, LTLAXIO5;
notations TARSKI, XBOOLE_0, ZFMISC_1, DOMAIN_1, SUBSET_1, PARTFUN1, XCMPLX_0,
NUMBERS, NAT_1, XXREAL_0, NAT_D, FUNCT_1, RELSET_1, FUNCT_2, FINSET_1,
FINSEQ_1, RFINSEQ, HILBERT1, HILBERT2, XBOOLEAN, MARGREL1, LTLAXIO1;
constructors NAT_D, RELSET_1, HILBERT2, RFINSEQ, DOMAIN_1, LTLAXIO1;
registrations SUBSET_1, ORDINAL1, NAT_1, XBOOLEAN, RELSET_1, MARGREL1,
XBOOLE_0, XREAL_0, HILBERT1, FINSET_1, LTLAXIO1;
requirements NUMERALS, BOOLE, SUBSET, ARITHM, REAL;
definitions TARSKI, XBOOLE_0, LTLAXIO1;
equalities XBOOLEAN, FINSEQ_1;
expansions TARSKI, LTLAXIO1;
theorems TARSKI, NAT_1, XBOOLE_0, XXREAL_0, FINSEQ_1, NAT_D, XBOOLEAN,
PARTFUN1, XREAL_1, ZFMISC_1, ORDINAL1, XREAL_0, FINSEQ_4, RFINSEQ,
RELAT_1, FINSEQ_5, FUNCT_1, FINSEQ_3, XBOOLE_1, LTLAXIO1, LTLAXIO2,
LTLAXIO4;
schemes NAT_1, FUNCT_2, RECDEF_1, FRAENKEL, FINSEQ_1;
begin
theorem Lm1:
for X be set,f be FinSequence of X,i be Nat st 1 <= i & i <= len f holds
f.i=f/.i
proof
let X be set,f be FinSequence of X,i be Nat;
assume 1 <= i & i <= len f; then
i in dom f by FINSEQ_3:25;
hence thesis by PARTFUN1:def 6;
end;
reserve A,B,C,D,p,q,r for Element of LTLB_WFF,
F,G,X for Subset of LTLB_WFF,
M for LTLModel,
i,j,n for Element of NAT,
f,f1,f2,g for FinSequence of LTLB_WFF;
::#INSERT: LTLB with normal semantics is monotonic
theorem mon2:
F c= G & F |- A implies G |- A
proof
assume A0: F c= G & F |- A;then
consider f such that
A1: f.len f = A & 1 <= len f and
A2: for i be Nat st 1<=i & i<=len f holds prc f,F,i;
now
let i be Nat;
assume 1<=i & i<=len f;then
per cases by LTLAXIO1:def 29,A2;
suppose f.i in F;
hence prc f,G,i by A0;
end;
suppose f.i in LTL_axioms or
(ex j,k be Nat st 1<=j & j* B) => ((B => C) => (A => C)) is LTL_TAUT_OF_PL
proof
let g be Function of LTLB_WFF,BOOLEAN;
set v = VAL g;
A1: v.A = 1 or v.A = 0 by XBOOLEAN:def 3;
A2: v.B = 1 or v.B = 0 by XBOOLEAN:def 3;
A3: v.C = 1 or v.C = 0 by XBOOLEAN:def 3;
thus v.((A => B) => ((B => C) => (A => C)))
= v.(A => B) => v.((B => C) => (A => C)) by LTLAXIO1:def 15
.= v.A => v.B => v.((B => C) => (A => C)) by LTLAXIO1:def 15
.= v.A => v.B => (v.(B => C) => v.(A => C)) by LTLAXIO1:def 15
.= v.A => v.B => ((v.B => v.C) => v.(A => C)) by LTLAXIO1:def 15
.= 1 by A1,A2,A3,LTLAXIO1:def 15;
end;
theorem th17:
(A => (B => C)) => ((A => B) => (A => C)) is LTL_TAUT_OF_PL
proof
let g be Function of LTLB_WFF,BOOLEAN;
set v = VAL g;
A1: v.A = 1 or v.A = 0 by XBOOLEAN:def 3;
A2: v.B = 1 or v.B = 0 by XBOOLEAN:def 3;
A3: v.C = 1 or v.C = 0 by XBOOLEAN:def 3;
thus v.((A => (B => C)) => ((A => B) => (A => C)))
= v.(A => (B => C)) => v.((A => B) => (A => C)) by LTLAXIO1:def 15
.= v.A => v.(B => C) => v.((A => B) => (A => C)) by LTLAXIO1:def 15
.= v.A => (v.B => v.C) => v.((A => B) => (A => C)) by LTLAXIO1:def 15
.= v.A => (v.B => v.C) => (v.(A => B) => v.(A => C)) by LTLAXIO1:def 15
.= v.A => (v.B => v.C) => ((v.A => v.B) => v.(A => C)) by LTLAXIO1:def 15
.= 1 by A1,A2,A3,LTLAXIO1:def 15;
end;
theorem th18:
F |- ('G' A) => A
proof
A1: {A} c= F \/ {A} by XBOOLE_1:7;
A in {A} by TARSKI:def 1;then
F \/ {A} |- A by A1,LTLAXIO1:42;
hence F |- ('G' A) => A by LTLAXIO1:57;
end;
theorem th19a:
{A} |= 'G' 'X' A
proof
assume not {A} |= 'G' 'X' A;then
consider M such that
A1: M |= {A} & not M |= 'G' 'X' A;
consider i such that
A2: not (SAT M).[i,'G' 'X' A] = 1 by A1;
consider j such that
A3: not (SAT M).[i+j,'X' A] = 1 by A2,LTLAXIO1:10;
A4: not (SAT M).[i+j+1,A] = 1 by A3,LTLAXIO1:9;
A in {A} by TARSKI:def 1;then
M |= A by A1;
hence contradiction by A4;
end;
theorem th19:
F |- ('G' A) => 'G' 'X' A
proof
{A} |- 'G' 'X' A by LTLAXIO4:33,th19a;then
F \/ {A} |- 'G' 'X' A by mon2,XBOOLE_1:7;
hence thesis by LTLAXIO1:57;
end;
theorem th20:
F |- ('G' (A => B)) => (('G' (A => 'X' A)) => ('G' (A => 'G' B)))
proof
A => B in {A =>B} by TARSKI:def 1;then
A => B in F \/ {A =>B} by XBOOLE_0:def 3;then
A => B in F \/ {A =>B} \/ {A => 'X' A} by XBOOLE_0:def 3;then
A1: F \/ {A =>B} \/ {A => 'X' A} |- A => B by LTLAXIO1:42;
A => 'X' A in {A => 'X' A} by TARSKI:def 1;then
A => 'X' A in F \/ {A =>B} \/ {A => 'X' A} by XBOOLE_0:def 3;then
F \/ {A =>B} \/ {A => 'X' A} |- A => 'X' A by LTLAXIO1:42;then
F \/ {A =>B} \/ {A => 'X' A} |- 'G' (A => 'G' B) by LTLAXIO1:45,54,A1;then
F \/ {A =>B} |- ('G' (A => 'X' A)) => 'G' (A => 'G' B) by LTLAXIO1:57;
hence thesis by LTLAXIO1:57;
end;
begin
::#INSERT: A formula A is initially valid in the temporal structure M
definition let M,A;
pred M |=0 A means (SAT M).[0,A]=1;
end;
::#INSERT: A set F of formulas is initially valid in the temporal structure M
definition let M,F;
pred M |=0 F means for A st A in F holds M |=0 A;
end;
::#INSERT: A formula A is an initial consequence of a set F of formulas
definition let F,A;
pred F |=0 A means
for M st M |=0 F holds M |=0 A;
end;
begin
::#INSERT: The numbers 2.6.1-2.6.8, put in comments in the article,
::#INSERT: correspond to the ones in: Kroeger, Merz. Temporal Logic and State
::#INSERT: Systems. 2008. Springer-Verlag.
::#INSERT: 2.6.1a-trivial: M |= A implies M |=0 A
theorem Th1:
M |= F implies M |=0 F
proof
assume Z1: M |= F;
let A;
assume A in F;then
M |= A by Z1;
hence M |=0 A;
end;
::#INSERT: 2.6.1b
theorem th261b:
M |= A iff M |=0 'G' A
proof
hereby assume M |= A;then
for i holds (SAT M).[0+i,A]=1;
hence M |=0 'G' A by LTLAXIO1:10;
end;
assume Z2: M |=0 'G' A;
now
let i;
(SAT M).[0+i,A]=1 by LTLAXIO1:10,Z2;
hence (SAT M).[i,A]=1;
end;
hence M |= A;
end;
::#INSERT: 2.6.2a
theorem th262a:
F |=0 A implies F |= A
proof
assume Z1: F |=0 A;
let M;
assume
A1: M |= F;
let i;
M^\i |=0 F by A1,LTLAXIO1:29,Th1;then
M^\i |=0 A by Z1;then
(SAT M).[i+0,A] =1 by LTLAXIO1:28;
hence (SAT M).[i,A]=1;
end;
definition let F;
func 'G' F -> Subset of LTLB_WFF equals
{'G' A where A is Element of LTLB_WFF: A in F};
correctness
proof
set s = {'G' A where A is Element of LTLB_WFF: A in F};
s c= LTLB_WFF
proof
let x be object;
assume x in s;
then ex A st x = 'G' A & A in F;
hence x in LTLB_WFF;
end;
hence thesis;
end;
end;
theorem th261bq:
M |= F iff M |=0 ('G' F)
proof
hereby assume Z1: M |= F;
thus M |=0 ('G' F)
proof
let A;
assume A in 'G' F;then
consider B such that
A1: A = 'G' B & B in F;
thus M |=0 A by A1,th261b,Z1;
end;
end;
assume Z1: M |=0 ('G' F);
let A;
assume A in F;then
'G' A in 'G' F;
hence M |= A by th261b,Z1;
end;
::#INSERT: 2.6.2b
theorem th262b:
F |= A iff 'G' F |=0 A
proof
hereby assume Z1: F |= A;
thus 'G' F |=0 A
proof
let M;
assume M |=0 'G' F;then
M |= A by Z1,th261bq;
hence M |=0 A;
end;
end;
assume Z2: 'G' F |=0 A;
thus F |= A
proof
let M;
assume Z3: M |= F;
let i;
M^\i |= F by LTLAXIO1:29,Z3;then
M^\i |=0 A by Z2,th261bq;then
(SAT M).[i+0,A] =1 by LTLAXIO1:28;
hence (SAT M).[i,A]=1;
end;
end;
theorem th262ac1:
{prop n} |= 'X' prop n & not {prop n} |=0 'X' prop n
proof
thus {prop n} |= 'X' prop n
proof
let M;
assume M |= {prop n};then
A2: M |= prop n by LTLAXIO1:23;
let i;
(SAT M).[i+1,prop n] = 1 by A2;
hence (SAT M).[i,'X' prop n]=1 by LTLAXIO1:9;
end;
thus not {prop n} |=0 'X' prop n
proof
defpred P[Element of NAT,Element of bool props] means
($1 = 0 implies $2 = {prop n}) &
(not $1 = 0 implies $2 = {}LTLB_WFF);
A3: for x being Element of NAT ex y being Element of bool props st P[x,y]
proof
let x being Element of NAT;
per cases;
suppose S1: x = 0;
prop n in props by LTLAXIO1:def 10;then
reconsider p0 = {prop n} as Element of bool props by ZFMISC_1:31;
P[x,p0] by S1;
hence ex y being Element of bool props st P[x,y];
end;
suppose S2:not x = 0;
reconsider e = {}LTLB_WFF as Element of bool props by XBOOLE_1:2;
P[x,e] by S2;
hence ex y being Element of bool props st P[x,y];
end;
end;
consider M being Function of NAT,bool props such that
A4: for x being Element of NAT holds P[x,M.x] from FUNCT_2:sch 3(A3);
reconsider M as LTLModel;
A5: M |=0 {prop n}
proof
let A;
assume A in {prop n};then
A6: A = prop n by TARSKI:def 1;
M.0 = {prop n} by A4;then
prop n in M.0 by TARSKI:def 1;
hence M |=0 A by LTLAXIO1:def 11,A6;
end;
not M |=0 'X' prop n
proof
assume M |=0 'X' prop n;then
(SAT M).[0+1,prop n]=1 by LTLAXIO1:9;then
prop n in M.1 by LTLAXIO1:def 11;
hence contradiction by A4;
end;
hence thesis by A5;
end;
end;
::#INSERT: The converse of 2.6.2a does not hold in general
theorem
ex F,A st F |= A & not F |=0 A
proof
{prop 0} |= 'X' prop 0 & not {prop 0} |=0 'X' prop 0 by th262ac1;
hence thesis;
end;
theorem th21:
F |=0 'G' A implies F |= A
proof
assume
Z1: F |=0 'G' A;
assume not F |= A;then
consider M such that
A1: M |= F & not M |= A;
A3: M |=0 F
proof
let A;
assume A in F;then
M |= A by A1;
hence M |=0 A;
end;
consider i such that
A2: not (SAT M).[i,A] = 1 by A1;
M |=0 'G' A by A3,Z1;then
(SAT M).[0+i,A] = 1 by LTLAXIO1:10;
hence contradiction by A2;
end;
theorem th21cp:
{prop i} |= prop i & not {prop i} |=0 'G' prop i
proof
thus {prop i} |= prop i
proof
let M;
A1: prop i in {prop i} by TARSKI:def 1;
assume M |= {prop i};
hence thesis by A1;
end;
not {prop i} |=0 'X' prop i by th262ac1;then
consider M such that
A2: M |=0 {prop i} & not M |=0 'X' prop i;
not (SAT M).[0+1,prop i] = 1 by LTLAXIO1:9,A2;then
not M |=0 'G' prop i by LTLAXIO1:10;
hence not {prop i} |=0 'G' prop i by A2;
end;
theorem
ex F, A st (F |= A & not F |=0 'G' A)
proof
{prop 0} |= prop 0 & not {prop 0} |=0 'G' prop 0 by th21cp;
hence thesis;
end;
theorem th263pa:
M |=0 F & M |=0 G iff M |=0 F\/G
proof
hereby assume A1: M |=0 F & M |=0 G;
thus M |=0 F\/G
proof
let A;
assume A in F\/G;
then A in F or A in G by XBOOLE_0:def 3;
hence M |=0 A by A1;
end;
end;
assume A2: M |=0 F\/G;
thus M |=0 F
proof
let A;
assume A in F;
then A in F\/G by XBOOLE_0:def 3;
hence M |=0 A by A2;
end;
let A;
assume A in G;
then A in F\/G by XBOOLE_0:def 3;
hence M |=0 A by A2;
end;
theorem th263pb:
M |=0 A iff M |=0 {A}
proof
thus M |=0 A implies M |=0 {A} by TARSKI:def 1;
A in {A} by TARSKI:def 1;
hence thesis;
end;
::#INSERT: 2.6.3
::#INSERT: In compare to normal consequence (LTLAXIO1:30), the relationship
::#INSERT: between implication and initial consequence holds in the classical
::#INSERT: form
theorem th263: :: 2.6.3
F\/{A} |=0 B iff F|=0 A=>B
proof
hereby assume A3:F\/{A} |=0 B;
thus F|=0 A=>B
proof
let M;
assume
A4: M |=0 F;
A2: (SAT M).[0,A=>B]= (SAT M).[0,A] => (SAT M).[0,B]
by LTLAXIO1:def 11;
thus M |=0 A=> B
proof
per cases by XBOOLEAN:def 3;
suppose (SAT M).[0,A] = 0;
hence (SAT M).[0,A=>B]= 1 by A2;
end;
suppose (SAT M).[0,A] = 1;then
M |=0 A;then
M |=0 {A} by th263pb;then
M |=0 B by A3,th263pa,A4;
hence (SAT M).[0,A=>B]= 1 by A2;
end;
end;
end;
end;
assume
A6: F|=0 A=>B;
let M;
assume M |=0 F\/{A};then
A5: M |=0 F & M |=0 {A} by th263pa;then
A7: M |=0 A by th263pb;
M |=0 A=>B by A5,A6;then
(SAT M).[0,A] => (SAT M).[0,B] = 1 by LTLAXIO1:def 11;
hence M |=0 B by A7;
end;
theorem th264p:
'G' {}LTLB_WFF = {}LTLB_WFF
proof
thus 'G' {}LTLB_WFF c= {}LTLB_WFF
proof
let x be object;
assume x in 'G' {}LTLB_WFF;then
consider A such that
A1: x = 'G' A & A in {}LTLB_WFF;
thus x in {}LTLB_WFF by A1;
end;
thus {}LTLB_WFF c= 'G' {}LTLB_WFF;
end;
::#INSERT: Universal validity concepts are equaivalent as far as
::#INSERT: initial and normal semantics is concerned:
::#INSERT: 2.6.4: one line proof:
::#INSERT: {}LTLB_WFF |= A iff {}LTLB_WFF |=0 A by th262b,th264p
::#INSERT: 2.1.8
theorem th218:
F |= A & (for B st B in F holds {}LTLB_WFF |= B)
implies {}LTLB_WFF |= A
proof
assume
Z1: F |= A & (for B st B in F holds {}LTLB_WFF |= B);
let M;
assume
Z2: M |= {}LTLB_WFF;
now
let B;
assume B in F;then
{}LTLB_WFF |= B by Z1;
hence M |= B by Z2;
end;then
M |= F;
hence M |= A by Z1;
end;
::#INSERT: 2.6.5
theorem th265:
F |= A & (for B st B in F holds {}LTLB_WFF |=0 B)
implies {}LTLB_WFF |=0 A
proof
assume
Z1: F |= A & (for B st B in F holds {}LTLB_WFF |=0 B);then
for B st B in F holds {}LTLB_WFF |= B by th262b,th264p;
hence {}LTLB_WFF |=0 A by th262b,th264p,th218,Z1;
end;
theorem
{}LTLB_WFF |=0 A implies {}LTLB_WFF |=0 'X' A
proof
assume Z1: {}LTLB_WFF |=0 A;
A1: {A} |= A by LTLAXIO1:23;
B in {A} implies {}LTLB_WFF |=0 B by TARSKI:def 1,Z1;
hence {}LTLB_WFF |=0 'X' A by th265,A1,LTLAXIO1:25;
end;
begin
::#INSERT: Axioms
definition
func LTL0_axioms -> Subset of LTLB_WFF equals
'G' LTL_axioms;
correctness;
end;
::#INSERT: Derivation rules
definition let p,q;
pred p REFL0_rule q means
p = 'G' q;
pred p NEX0_rule q means
ex A st p = 'G' A & q = 'G' 'X' A;
let r;
pred p,q MP0_rule r means
ex A,B st p='G' A & q= 'G' (A=>B) & r='G' B;
pred p,q IND0_rule r means
ex A,B st p='G' (A=>B) & q= 'G' (A=>('X' A)) & r='G' (A=>('G' B));
end;
::#INSERT: Definition of derivation step
definition let i be Nat,f,X;
pred prc0 f,X,i means :Def29:
f.i in LTL0_axioms or f.i in X
or (ex j,k be Nat st 1<=j & j** & 1<=len f1 &
for i be Nat st 1<=i & i<=len f1 holds prc0 f1,X,i) &
prc0 f,X,len f implies (for i be Nat st 1<=i & i<=len f holds prc0 f,X,i) &
X |-0 p
proof
assume that
A1: f=f1^<*p*> and
1<=len f1 and
A2: for i be Nat st 1<=i & i<=len f1 holds prc0 f1,X,i;
A3: len f=(len f1+len<*p*>) by A1,FINSEQ_1:22
.=len f1+1 by FINSEQ_1:39;
assume A4: prc0 f,X,len f;
A5: 0+len f1<=len f by A3,NAT_1:12;
A6: now let i be Nat;
assume that
A7: 1<=i and
A8: i<=len f;
A9: i) by A1,FINSEQ_1:22
.=f.(len f1+1) by FINSEQ_1:39
.=p by A1,FINSEQ_1:42;
hence X |-0 p by A3,XREAL_1:31,A6;
end;
begin
::#INSERT: Axioms are sound
theorem Th2:
A in LTL0_axioms implies F |=0 A
proof
assume A in LTL0_axioms;then
consider B such that
A8: A = 'G' B & B in LTL_axioms;
{}LTLB_WFF |- B by LTLAXIO1:42,A8;then
{}LTLB_WFF |= 'G' B by LTLAXIO1:41,54;then
B1: {}LTLB_WFF |=0 'G' B by th262b,th264p;
let M;
assume M |=0 F;
M |=0 {}LTLB_WFF;
hence M |=0 A by B1,A8;
end;
::#INSERT: MP_rule is sound
theorem Th3:
F |=0 A & F |=0 A=>B implies F |=0 B
proof
assume that
A1: F |=0 A and
A2: F |=0 A=>B;
let M;
assume
B3: M |=0 F;then
M |=0 A=>B by A2;then
B6: (SAT M).[0,A] => (SAT M).[0,B] = 1 by LTLAXIO1:def 11;
M |=0 A by A1,B3;
hence M |=0 B by B6;
end;
::#INSERT: MP0_rule is sound
theorem Th4:
F |=0 'G' A & F |=0 'G' (A=>B) implies F |=0 'G' B
proof
assume that
A1: F |=0 'G' A and
A2: F |=0 'G' (A=>B);
let M;
assume
B10: M |=0 F;then
B11: M |=0 'G' A by A1;
B12: M |=0 'G' (A=>B) by B10,A2;
now
let i;
B13: (SAT M).[0+i,A]=1 by B11,LTLAXIO1:10;
(SAT M).[0+i,A=>B]=1 by B12,LTLAXIO1:10;then
(SAT M).[i,A] => (SAT M).[i,B] = 1 by LTLAXIO1:def 11;
hence (SAT M).[0+i,B]=1 by B13;
end;
hence M |=0 'G' B by LTLAXIO1:10;
end;
::#INSERT: NEX0_rule is sound
theorem Th5:
F |=0 'G' A implies F |=0 'G' 'X' A
proof
assume A1: F |=0 'G' A;
let M;
assume M |=0 F;then
A3: M |=0 'G' A by A1;
now
let i be Element of NAT;
(SAT M).[0+(i+1),A] = 1 by LTLAXIO1:10,A3;
hence (SAT M).[0+i,'X' A] = 1 by LTLAXIO1:9;
end;
hence M |=0 'G' 'X' A by LTLAXIO1:10;
end;
::#INSERT: REFL0_rule is sound
theorem Th6:
F |=0 'G' A implies F |=0 A
proof
assume Z1: F |=0 'G' A;
let M;
assume M |=0 F;then
M |=0 'G' A by Z1;then
(SAT M).[0+0,A]=1 by LTLAXIO1:10;
hence (SAT M).[0,A]=1;
end;
::#INSERT: IND0_rule is sound
theorem Th7:
F |=0 'G' (A=>B) & F |=0 'G' (A=>('X' A)) implies F |=0 'G' (A=>('G' B))
proof
assume that
A1: F |=0 'G' (A=>B) and
A2: F |=0 'G' A=>('X' A);
let M;
assume A3: M |=0 F;
now
let n be Element of NAT;
defpred P1[Nat] means
(SAT M).[n+$1,A]=1;
per cases by XBOOLEAN:def 3;
suppose A4: (SAT M).[n,A]=1;
A5: for k being Nat st P1[k] holds P1[k+1]
proof
let k be Nat such that
A6: P1[k];
reconsider kk=k as Element of NAT by ORDINAL1:def 12;
M |=0 'G' (A=>('X' A)) by A2,A3;then
(SAT M).[0+(n+kk),A=>('X' A)]=1 by LTLAXIO1:10;
then (SAT M).[n+kk,A]=>(SAT M).[n+kk,'X' A]=1 by LTLAXIO1:def 11;
then (SAT M).[n+kk+1,A]=1 by A6,LTLAXIO1:9;
hence P1[k+1];
end;
A7: P1[0] by A4;
A8: for i be Nat holds P1[i] from NAT_1:sch 2(A7,A5);
now
let i be Element of NAT;
M |=0 'G' (A => B) by A1,A3;then
(SAT M).[0+(n+i),A=>B]=1 by LTLAXIO1:10;
then A9: (SAT M).[n+i,A]=>(SAT M).[n+i,B]=1 by LTLAXIO1:def 11;
(SAT M).[n+i,A]=1 by A8;
hence (SAT M).[n+i,B]=1 by A9;
end;
then (SAT M).[n,'G' B]=1 by LTLAXIO1:10;
then (SAT M).[n,A]=>(SAT M).[n,'G' B]=1;
hence (SAT M).[0+n,A=>('G' B)]=1 by LTLAXIO1:def 11;
end;
suppose(SAT M).[n,A]=0;
then (SAT M).[n,A]=>(SAT M).[n,'G' B]=1;
hence (SAT M).[0+n,A=>('G' B)]=1 by LTLAXIO1:def 11;
end;
end;
hence M |=0 'G' (A=>('G' B)) by LTLAXIO1:10;
end;
::#INSERT: 2.6.6
::$N Soundness Theorem for LTLB with initial semantics.
theorem th266:
F |-0 A implies F |=0 A
proof
assume F |-0 A;
then consider f such that
A1: f.len f=A and
A2: 1<=len f and
A3: for i be Nat st 1<=i & i<=len f holds prc0 f,F,i;
defpred P[Nat] means
1<=$1 & $1<=len f implies F |=0 f/.$1;
A4: for i being Nat st for j being Nat st j**f/.i by A15,A5,A12,A13;
hence F |=0 f/.i by A5,A10,A11,A16,Th3;
end;
suppose f/.j,f/.k MP0_rule f/.i;then
consider A,B such that
B7: f/.j = 'G' A and
B8: f/.k= 'G' (A=>B) and
B9: f/.i = 'G' B;
thus F |=0 f/.i by Th4,B7,B8,B9,A15a,B5;
end;
suppose f/.j,f/.k IND0_rule f/.i;
then consider A,B such that
A17: f/.j= 'G' (A=>B) and
A18: f/.k= 'G' (A=>('X' A)) & f/.i = 'G' (A=>('G' B));
F |=0 'G' (A=>B) by A5,A10,A11,A16,A17;
hence F |=0 f/.i by A15a,A18,Th7;
end;
end;
suppose ex j be Nat st 1<=j & j**;
A4: len g=len f+len<*A*> by FINSEQ_1:22
.=len f+1 by FINSEQ_1:39;
then A5: len f;
A4: len g=len f+len<*('G' 'X' A)*> by FINSEQ_1:22
.=len f+1 by FINSEQ_1:39;
then A5: len f B implies F |-0 B
proof
assume that
A1: F |-0 A and
A2: F|-0 A => B;
consider f such that
A3: f.len f= A and
A4: 1<=len f and
A5: for i be Nat st 1<=i & i<=len f holds prc0 f,F,i by A1;
consider g such that
A6: g.len g= A => B and
A7: 1<=len g and
A8: for i be Nat st 1<=i & i<=len g holds prc0 g,F,i by A2;
A9: for i be Nat st 1<=i & i<=len(f^g) holds prc0 f^g,F,i by A4,A5,A7,A8,Th39;
set h=f^g^<*B*>;
A10: h=f^(g^<*B*>) by FINSEQ_1:32;
A11: len(f^g)=len f+len g by FINSEQ_1:22;
then A12: 1<=len(f^g) by A4,NAT_1:12;
A13: len h=len(f^g)+len<*B*> by FINSEQ_1:22
.=len(f^g)+1 by FINSEQ_1:39;
then 1<=len h by A4,A11,NAT_1:16;
then A14: h/.len h=h.len h by Lm1
.= B by A13,FINSEQ_1:42;
len h=len f+(len g+1) by A11,A13;
then A15: len f B by A6,A7,FINSEQ_1:65;
then h/.len f,h/.len(f^g) MP_rule h/.len h by A16,A14;
then prc0 h,F,len h by A4,A12,A15,A17;
hence F |-0 B by A12,A9,Th40;
end;
::#INSERT: MP0_rule is derivable
theorem th11:
F |-0 'G' A & F |-0 'G' (A => B) implies F |-0 'G' B
proof
assume that
A1: F |-0 'G' A and
A2: F|-0 'G' (A => B);
consider f such that
A3: f.len f= 'G' A and
A4: 1<=len f and
A5: for i be Nat st 1<=i & i<=len f holds prc0 f,F,i by A1;
consider g such that
A6: g.len g= 'G' (A => B) and
A7: 1<=len g and
A8: for i be Nat st 1<=i & i<=len g holds prc0 g,F,i by A2;
A9: for i be Nat st 1<=i & i<=len(f^g) holds prc0 f^g,F,i by A4,A5,A7,A8,Th39;
set h=f^g^<*('G' B)*>;
A10: h=f^(g^<*('G' B)*>) by FINSEQ_1:32;
A11: len(f^g)=len f+len g by FINSEQ_1:22;
then A12: 1<=len(f^g) by A4,NAT_1:12;
A13: len h=len(f^g)+len<*('G' B)*> by FINSEQ_1:22
.=len(f^g)+1 by FINSEQ_1:39;
then 1<=len h by A4,A11,NAT_1:16;
then A14: h/.len h=h.len h by Lm1
.= 'G' B by A13,FINSEQ_1:42;
len h=len f+(len g+1) by A11,A13;
then A15: len f B) by A6,A7,FINSEQ_1:65;
then h/.len f,h/.len(f^g)MP0_rule h/.len h by A16,A14;
then prc0 h,F,len h by A4,A12,A15,A17;
hence F |-0 'G' B by A12,A9,Th40;
end;
::#INSERT: IND0_rule is derivable
theorem th13:
F |-0 'G' (A=>B) & F |-0 'G' (A => 'X' A) implies F |-0 'G' (A => 'G' B)
proof
assume that
A1: F |-0 'G' (A=>B) and
A2: F|-0 'G' (A => 'X' A);
consider f such that
A3: f.len f= 'G' (A=>B) and
A4: 1<=len f and
A5: for i be Nat st 1<=i & i<=len f holds prc0 f,F,i by A1;
consider g such that
A6: g.len g= 'G' (A => 'X' A) and
A7: 1<=len g and
A8: for i be Nat st 1<=i & i<=len g holds prc0 g,F,i by A2;
A9: for i be Nat st 1<=i & i<=len(f^g) holds prc0 f^g,F,i by A4,A5,A7,A8,Th39;
set h=f^g^<*('G' (A => 'G' B))*>;
A10: h=f^(g^<*('G' (A => 'G' B))*>) by FINSEQ_1:32;
A11: len(f^g)=len f+len g by FINSEQ_1:22;
then A12: 1<=len(f^g) by A4,NAT_1:12;
A13: len h=len(f^g)+len<*('G' (A => 'G' B))*> by FINSEQ_1:22
.=len(f^g)+1 by FINSEQ_1:39;
then 1<=len h by A4,A11,NAT_1:16;
then A14: h/.len h=h.len h by Lm1
.= 'G' (A => 'G' B) by A13,FINSEQ_1:42;
len h=len f+(len g+1) by A11,A13;
then A15: len fB) by A3,A4,A10,FINSEQ_1:64;
A17: len(f^g) 'X' A) by A6,A7,FINSEQ_1:65;
then h/.len f,h/.len(f^g) IND0_rule h/.len h by A16,A14;
then prc0 h,F,len h by A4,A12,A15,A17;
hence F |-0 'G' (A => 'G' B) by A12,A9,Th40;
end;
theorem th15:
A in LTL_axioms implies F|-0 A
proof
assume A in LTL_axioms;then
'G' A in LTL0_axioms;then
F|-0 'G' A by th10;
hence F|-0 A by th9;
end;
theorem
A in LTL0_axioms implies F |- A
proof
assume A in LTL0_axioms;then
consider B such that
A1: A = 'G' B & B in LTL_axioms;
F |- B by A1,LTLAXIO1:42;
hence F|- A by A1,LTLAXIO1:54;
end;
::#INSERT: 2.6.7
::#INSERT: auxilliary theorem to prove completeness theorem
theorem th267:
{}LTLB_WFF |- A implies {}LTLB_WFF |-0 A
proof
assume {}LTLB_WFF |- A;then
consider f such that
A1: f.len f = A and
A2: 1<=len f and
A3: for i be Nat st 1<=i & i<=len f holds prc f,{}LTLB_WFF,i;
defpred P[Nat] means 1<=$1 & $1<=len f implies {}LTLB_WFF |-0 'G' f/.$1;
A4: for i being Nat st for j being Nat st j** C and
A25: f/.k= B => ('X' B) and
A26: f/.i= B => ('G' C);
thus thesis by A24,A25,A26,th13,A20,A21;
end;
end;
suppose ex j be Nat st 1<=j & j** FinSequence of LTLB_WFF means :imps:
len it = len f & it.1 = f/.1 => A & for i st
1 <= i & i < len f holds it.(i+1) = f/.(i+1) => it/.i if len f > 0
otherwise it = <*> LTLB_WFF;
existence
proof
defpred P[Nat,set,set] means
ex A,B st A = $2 & B = $3 & B = f/.($1 + 1) => A;
A1: now
let n be Nat;
assume 1 <= n & n < len f;
let x being Element of LTLB_WFF;
P[n,x,f/.(n+1) => x];
hence ex y being Element of LTLB_WFF st P[n,x,y];
end;
consider p being FinSequence of LTLB_WFF such that
A2: len p = len f & (p.1 = f/.1 => A or len f = 0) & for n being Nat
st 1 <= n & n < len f holds P[n,p.n,p.(n+1)] from RECDEF_1:sch 4(A1);
thus len f > 0 implies ex p be FinSequence of LTLB_WFF st len p = len f &
p.1 = f/.1 => A &
for i st 1 <= i & i < len f holds p.(i+1) = f/.(i+1) => p/.i
proof
assume
A3: len f > 0;
take p;
now
let i;
assume
A4: 1 <= i & i < len f;then
ex A,B st A = p.i & B = p.(i+1) & B = f/.(i + 1) => A by A2;
hence p.(i+1) = f/.(i+1) => p/.i by FINSEQ_4:15, A4,A2;
end;
hence thesis by A2,A3;
end;
thus thesis;
end;
uniqueness
proof
let f1,f2 be FinSequence of LTLB_WFF;
thus len f > 0 & len f1 = len f & f1.1 = f/.1 => A &
(for i st 1 <= i & i < len f holds f1.(i+1) = ( f/.(i+1)) => f1/.i) &
len f2 = len f & f2.1 = ( f/.1) => A & (for i st 1 <= i & i < len f
holds f2.(i+1) = (f/.(i+1)) => f2/.i) implies f1 = f2
proof
assume that
A5: len f > 0 and
A6: len f1 = len f and
A7: f1.1 = f/.1 => A and
A8: for i st 1 <= i & i < len f holds f1.(i+1) = ( f/.(i+1)) => f1/. i
and
A9: len f2 = len f and
A10: f2.1 = ( f/.1) => A and
A11: for i st 1 <= i & i < len f holds f2.(i+1) = ( f/.(i+1)) => f2/. i;
A12: 1 <= len f2 by A9,NAT_1:25,A5;
1 <= len f1 by A6,NAT_1:25,A5;
then A13: f1/.1 = f1.1 by FINSEQ_4:15
.= f2/.1 by FINSEQ_4:15,A12,A10,A7;
A14: now
defpred P[Nat] means
$1 < len f implies f1.($1+1) = f2.($1+1);
let n;
set m = n -' 1;
assume
n in dom f1;
then A15: n in Seg len f1 by FINSEQ_1:def 3;
then 1 <= n by FINSEQ_1:1;
then 1 + (-1) <= n + (-1) by XREAL_1:6;
then A16: m = n - 1 by XREAL_0:def 2;
then A17: m + 1 <= len f by A6, A15,FINSEQ_1:1;
A18: for i being Nat st P[i] holds P[i + 1]
proof
let i be Nat;
assume
A19: P[i];
assume
A20: i + 1 < len f;
A21: 1 <= i + 1 by NAT_1:25;
per cases by NAT_1:25;
suppose
i = 0;
hence f1.(i+1+1) = ( f/.(i+1+1)) => f2/.(i+1) by A13,A20,A8
.= f2.(i+1+1) by A20,A21,A11;
end;
suppose
i >= 1;
A22: f1/.(i+1) = f1.(i+1) by FINSEQ_4:15, A6,A20,A21
.= f2/.(i+1) by FINSEQ_4:15, A9,A20,A19,NAT_1:12;
thus f1.(i+1+1) = ( f/.(i+1+1)) => f1/.(i+1) by A20,A21 ,A8
.= f2.(i+1+1) by A20,A21,A11,A22;
end;
end;
A23: P[0] by A7,A10;
A24: for i being Nat holds P[i] from NAT_1:sch 2(A23,A18);
thus f1.n = f2.n by A16,A24, A17,XREAL_1:145;
end;
dom f1 = dom f2 by FINSEQ_3:29,A6,A9;
hence thesis by A14,PARTFUN1:5;
end;
thus thesis;
end;
consistency;
end;
::#INSERT: 2.6.8
::$N Weak Completeness Theorem for LTLB with initial semantics
theorem th268:
for F be finite Subset of LTLB_WFF holds F |=0 A implies F |-0 A
proof
let F be finite Subset of LTLB_WFF;
assume
Z1: F |=0 A;
per cases;
suppose
S1: F is empty;then
F |= A by th262b,th264p,Z1;
hence F |-0 A by th267,S1,LTLAXIO4:33;
end;
suppose
S2: not F is empty;
consider f be FinSequence such that
A4: rng f = F & f is one-to-one by FINSEQ_4:58;
reconsider f as FinSequence of LTLB_WFF by A4,FINSEQ_1:def 4;
A6: 1 <= len f by RELAT_1:38,A4,FINSEQ_1:20,S2;
then 1 <= len implications(f,A) by imps;
then A7: implications(f,A)/.1 = implications(f,A).1 by FINSEQ_4:15;
defpred P[Nat] means
1 <= $1 & $1 <= len f implies rng (f /^ $1) |=0 implications(f,A)/.$1;
rng (f|1) = rng <*f/.1*> by FINSEQ_5:20, RELAT_1:38,A4,S2;then
A8: rng (f /^ 1) \/ {f/.1} = rng (f|1) \/ rng (f /^ 1) by FINSEQ_1:38
.= rng ((f|1) ^ (f /^ 1)) by FINSEQ_1:31
.= rng f by RFINSEQ:8;
A9: len implications(f,A) = len f by A6,imps;
A10: now
let i be Nat;
A11: i in NAT by ORDINAL1:def 12;
assume
A12: P[i];
thus P[i + 1]
proof
assume that
A13: 1 <= i+1 and
A14: i+1 <= len f;
per cases by NAT_1:25;
suppose
A15: i = 0;
f/.1 => A = implications(f,A).1 by imps,A6
.= implications(f,A)/.1 by FINSEQ_4:15,A9,A6;
hence rng (f /^ (i+1)) |=0 implications(f,A)/.(i+1)
by A8,A4,Z1,th263,A15;
end;
suppose
A16: 1 <= i;
i+1 in dom f by FINSEQ_3:25,A13,A14;then
rng (<*f/.(i+1)*>^(f /^ (i+1))) |=0 implications(f,A)/.i
by A12,A16,NAT_1:13,A14,FINSEQ_5:31;then
rng <*f/.(i+1)*> \/ rng (f /^ (i+1)) |=0 implications(f,A)/.i
by FINSEQ_1:31;then
A17: rng (f /^ (i+1)) \/ {f/.(i+1)} |=0 implications(f,A)/.i
by FINSEQ_1:38;
A18: i < len f by NAT_1:13,A14;
implications(f,A)/.(i+1) = implications(f,A).(i+1)
by FINSEQ_4:15,A13,A14,A9
.= f/.(i+1) => implications(f,A)/.i by imps,A16,A18,A11;
hence rng (f /^ (i+1)) |=0 implications(f,A)/.(i+1) by A17,th263;
end;
end;
end;
A19:P[0];
for i be Nat holds P[i] from NAT_1:sch 2(A19,A10);then
rng (f /^ (len f)) |=0 implications(f,A)/.(len f) by A6;then
{} LTLB_WFF |=0 implications(f,A)/.(len f) by RFINSEQ:27,RELAT_1:38;then
D2: {} LTLB_WFF |- implications(f,A)/.(len f) by LTLAXIO4:33,th262b,th264p;
defpred P[Nat] means $1 < len f implies
rng f |-0 implications(f,A)/.(len f -' $1);
A21:now
let i be Nat;
assume
A22: P[i];
thus P[i+1]
proof
set j = len f -' (i+1);
assume
A23: i + 1 < len f;then
A24: i + 1 + (- (i +1)) < len f + (-(i + 1)) by XREAL_1:8;then
A25: j = len f - (i+1) by XREAL_0:def 2;then
A26: 1 <= j by NAT_1:25, A24;
i < len f by A23,NAT_1:12;then
len f + (-i) > i + (-i) by XREAL_1:8;then
A27: len f - i > 0;
A28: j + 1 = len f - (i + 1) + 1 by XREAL_0:def 2, A24
.= len f -' i by XREAL_0:def 2,A27;
A29: len f + (-i) <= len f by XREAL_1:32;then
j + 1 <= len f by A25;then
A30: j < len f by NAT_1:16,XXREAL_0:2;
j + 1 <= len implications(f,A) by A29,A25,imps;then
E5: implications(f,A)/.(len f -' i) = implications(f,A).(j + 1)
by A28,FINSEQ_4:15, NAT_1:11
.= (f/.(j + 1)) => implications(f,A)/.j by imps,A26, A30;
E9: j + 1 in dom f by FINSEQ_3:25, NAT_1:11, A29,A25;then
f.(j+1) in rng f by FUNCT_1:3;then
f/.(j+1) in rng f by PARTFUN1:def 6,E9;then
rng f |-0 f/.(j+1) by th10;
hence rng f |-0 implications(f,A)/.j by th11a,E5,A22,A23,NAT_1:12;
end;
end;
{}LTLB_WFF c= rng f;then
D3: rng f |-0 implications(f,A)/.len f by mon,D2,th267;
len f - 0 >= 1 by RELAT_1:38,A4,S2,FINSEQ_1:20;then
A33: P[0] by D3,XREAL_0:def 2;
A34: for i be Nat holds P[i] from NAT_1:sch 2(A33,A21);
1 + (-1) <= len f + (-1) by XREAL_1:6,FINSEQ_1:20,RELAT_1:38,A4,S2;
then len f -' 1 = len f - 1 by XREAL_0:def 2;
then reconsider i = len f -1 as Element of NAT;
A32: len f + (- 1) < len f by XREAL_1:37;
len f -' i = len f - i by XREAL_0:def 2 .= 1;then
rng f |-0 implications(f,A)/.1 by A34,A32;then
C2: F |-0 (f/.1) => A by A4,imps,A7,A6;
C3: 1 in dom f by A6,FINSEQ_3:25;then
f.1 in rng f by FUNCT_1:3;then
f/.1 in rng f by PARTFUN1:def 6,C3;then
F |-0 f/.1 by A4,th10;
hence F |-0 A by C2,th11a;
end;
end;
begin
::#INSERT: Deduction theorem holds in the classical form compared with
::#INSERT: Deduction theorem for LTLB with normal semantics (see LTLAXIO1:57)
theorem
F \/ {A} |-0 B implies F |-0 A => B
proof
assume F \/ {A} |-0 B;then
consider f such that
A1: f.len f = B and
A2: 1<=len f and
A3: for i be Nat st 1<=i & i<=len f holds prc0 f,F \/ {A},i;
defpred P[Nat] means
1<=$1 & $1<=len f implies F |-0 A => f/.$1;
A4: for i being Nat st for j being Nat st j** (A=>f/.i) by th15,LTLAXIO1:34;
f/.i in LTL0_axioms by A6,A7,A8,Lm1;
then F |-0 f/.i by th10;
hence thesis by A9,th11a;
end;
suppose A10: f.i in F \/ {A};
per cases by A10,XBOOLE_0:def 3;
suppose A11: f.i in F;
A12: F |-0 f/.i=>(A=>f/.i) by th15,LTLAXIO1:34;
f/.i in F by A6,A7,A11,Lm1;
then F |-0 f/.i by th10;
hence thesis by A12,th11a;
end;
suppose f.i in {A};then
f.i=A by TARSKI:def 1;then
B1: f/.i=A by A6,A7,Lm1;
A => A is LTL_TAUT_OF_PL by LTLAXIO2:24;then
A => A in LTL_axioms by LTLAXIO1:def 17;
hence thesis by B1,th15;
end;
end;
suppose ex j,k be Nat st 1<=j & j** f/.j by A5,A15,A16;
k<=len f by A7,A18,XXREAL_0:2;then
A21: F|-0 A => f/.k by A5,A17,A18;
per cases by A19;
suppose A22: f/.j,f/.k MP_rule f/.i;
A23: F |-0 (A=>(f/.j=>f/.i))=>((A=>f/.j)=>(A=>f/.i))
by th15,LTLAXIO1:35;
F|-0 (A=>f/.j)=>(A=>f/.i) by A23,th11a,A21,A22;
hence F |-0 A => f/.i by A20,th11a;
end;
suppose f/.j,f/.k MP0_rule f/.i;
then consider C,D such that
A24: f/.j= 'G' C and
A25: f/.k= 'G' (C => D) and
A26: f/.i= 'G' D;
B1: {}LTLB_WFF c= F;
{}LTLB_WFF |-0 f/.k => (f/.j => f/.i)
by th267,LTLAXIO1:60,A24,A25,A26;then
B2: F |-0 f/.k => (f/.j => f/.i) by mon,B1;
(A => f/.k) => ((f/.k => (f/.j => f/.i))
=> (A => (f/.j => f/.i))) is LTL_TAUT_OF_PL by th16;then
(A => f/.k) => ((f/.k => (f/.j => f/.i))
=> (A => (f/.j => f/.i))) in LTL_axioms by LTLAXIO1:def 17;then
F |-0 (A => f/.k) => ((f/.k =>
(f/.j => f/.i)) => (A => (f/.j => f/.i))) by th15;then
F |-0 ((f/.k => (f/.j => f/.i))
=> (A => (f/.j => f/.i))) by th11a,A21;then
B3: F |-0 A => (f/.j => f/.i) by B2,th11a;
(A => (f/.j => f/.i)) => ((A => f/.j) => (A => f/.i))
is LTL_TAUT_OF_PL by th17;then
(A => (f/.j => f/.i)) => ((A => f/.j) => (A => f/.i))
in LTL_axioms by LTLAXIO1:def 17;then
F |-0 (A => (f/.j => f/.i))
=> ((A => f/.j) => (A => f/.i)) by th15;then
F |-0 (A => f/.j) => (A => f/.i) by th11a,B3;
hence F|-0 A => f/.i by th11a,A20;
end;
suppose f/.j,f/.k IND0_rule f/.i;
then consider C,D such that
A24: f/.j = 'G' (C=>D) and
A25: f/.k= 'G' (C => ('X' C)) and
A26: f/.i= 'G' (C => ('G' D));
A => f/.j => (A => f/.k => (A => (f/.j '&&' f/.k)))
is LTL_TAUT_OF_PL by LTLAXIO2:40;then
A => f/.j => (A => f/.k => (A => (f/.j '&&' f/.k)))
in LTL_axioms by LTLAXIO1:def 17;then
F |-0 A => f/.j => (A => f/.k => (A => (f/.j '&&' f/.k)))
by th15;then
F |-0 A => f/.k => (A => (f/.j '&&' f/.k))
by th11a,A20;then
B10: F |-0 A => (f/.j '&&' f/.k) by th11a,A21;
B12: {}LTLB_WFF c= F;
{}LTLB_WFF |- f/.j => (f/.k => f/.i) by th20,A24,A25,A26;then
{}LTLB_WFF |- (f/.j '&&' f/.k) => f/.i by LTLAXIO1:48;then
B11: F |-0 (f/.j '&&' f/.k) => f/.i by mon,B12,th267;
(A => (f/.j '&&' f/.k)) => (((f/.j '&&' f/.k) => f/.i)
=> (A => f/.i)) is LTL_TAUT_OF_PL by th16;then
(A => (f/.j '&&' f/.k)) => (((f/.j '&&' f/.k) => f/.i)
=> (A => f/.i)) in LTL_axioms by LTLAXIO1:def 17;then
F |-0 (A => (f/.j '&&' f/.k)) => (((f/.j '&&' f/.k) => f/.i)
=> (A => f/.i)) by th15;then
F |-0 (((f/.j '&&' f/.k) => f/.i) => (A => f/.i)) by th11a,B10;
hence thesis by th11a,B11;
end;
end;
suppose ex j be Nat st 1<=j & j** f/.j by A5,A32,A33;
per cases by A34;
suppose f/.j NEX0_rule f/.i;
then consider C such that
A24: f/.j= 'G' C and
A26: f/.i= 'G' 'X' C;
B8: {}LTLB_WFF c= F;
{}LTLB_WFF |-0 f/.j => f/.i by th19,th267,A24,A26;then
B9: F |-0 f/.j => f/.i by mon,B8;
(A => f/.j) => ((f/.j => f/.i) => (A => f/.i))
is LTL_TAUT_OF_PL by th16;then
(A => f/.j) => ((f/.j => f/.i) => (A => f/.i))
in LTL_axioms by LTLAXIO1:def 17;then
F |-0 (A => f/.j) => ((f/.j => f/.i) => (A => f/.i))
by th15;then
F |-0 ((f/.j => f/.i) => (A => f/.i)) by th11a,B4a;
hence thesis by B9,th11a;
end;
suppose f/.j REFL0_rule f/.i;then
B6: F |-0 A => 'G' f/.i by B4,A5,A32,A33;
B5: {}LTLB_WFF c= F;
{}LTLB_WFF |-0 ('G' f/.i) => f/.i by th267,th18;then
B7: F |-0 ('G' f/.i) => f/.i by mon,B5;
(A => ('G' f/.i)) => ((('G' f/.i) => f/.i) => (A => f/.i)) is
LTL_TAUT_OF_PL by th16;then
(A => ('G' f/.i)) => ((('G' f/.i) => f/.i) => (A => f/.i)) in
LTL_axioms by LTLAXIO1:def 17;then
F |-0 (A => ('G' f/.i)) => ((('G' f/.i) => f/.i) => (A => f/.i))
by th15;then
F |-0 ((('G' f/.i) => f/.i) => (A => f/.i)) by B6,th11a;
hence thesis by th11a,B7;
end;
end;
end;
end;
A37: for i be Nat holds P[i] from NAT_1:sch 4(A4);
B = f/.len f by A1,A2,Lm1;
hence F |-0 A => B by A2,A37;
end;
:: Converse of Deduction Theorem
theorem
F |-0 A => B implies F \/ {A} |-0 B
proof
A in {A} by TARSKI:def 1;
then A in F\/{A} by XBOOLE_0:def 3;then
A1: F\/{A} |-0 A by th10;
assume F |-0 A =>B;
then F\/{A} |-0 A =>B by mon,XBOOLE_1:7;
hence F\/{A} |-0 B by A1,th11a;
end;
begin
registration let F be finite Subset of LTLB_WFF;
cluster 'G' F -> finite;
coherence
proof
deffunc H(Element of LTLB_WFF) = 'G' $1;
A1: F is finite;
{H(w) where w is Element of LTLB_WFF: w in F} is finite
from FRAENKEL:sch 21(A1);
hence 'G' F is finite;
end;
end;
theorem
for F be finite Subset of LTLB_WFF holds (F |- A iff 'G' F |-0 A)
proof
let F be finite Subset of LTLB_WFF;
hereby assume F |- A;then
F |= A by LTLAXIO1:41;
hence 'G' F qua finite Subset of LTLB_WFF |-0 A by th268,th262b;
end;
assume 'G' F |-0 A;then
'G' F |=0 A by th266;
hence F |- A by LTLAXIO4:33,th262b;
end;
theorem
for F be finite Subset of LTLB_WFF holds (F |-0 A implies F |- A)
proof
let F be finite Subset of LTLB_WFF;
assume F |-0 A;then
F |=0 A by th266;
hence F |- A by LTLAXIO4:33,th262a;
end;
::#INSERT: The counterexample that "for F,A holds (F |- A implies F |-0 A)"
::#INSERT: is not true. Another counterexample see above for theorem "th14".
theorem
{prop i} |- 'G' prop i & not {prop i} |-0 'G' prop i
proof
thus {prop i} |- 'G' prop i
proof
prop i in {prop i} by TARSKI:def 1;then
{prop i} |- prop i by LTLAXIO1:42;
hence thesis by LTLAXIO1:54;
end;
thus not {prop i} |-0 'G' prop i
proof
assume {prop i} |-0 'G' prop i;then
A2: {prop i} |=0 'G' prop i by th266;
not {prop i} |=0 'X' prop i by th268,th14;then
consider M such that
A1: M |=0 {prop i} & not M |=0 'X' prop i;
M |=0 'G' prop i by A2,A1;then
(SAT M).[0+1,prop i] =1 by LTLAXIO1:10;
hence contradiction by LTLAXIO1:9,A1;
end;
end;
theorem
for F be finite Subset of LTLB_WFF holds (F |-0 'G' A implies F |- A)
proof
let F be finite Subset of LTLB_WFF;
assume F |-0 'G' A; then
F |=0 'G' A by th266;
hence F |- A by LTLAXIO4:33,th21;
end;
::#INSERT: The converse of the above theorem does not hold
theorem
{prop i} |- prop i & not {prop i} |-0 'G' prop i
proof
prop i in {prop i} by TARSKI:def 1;
hence {prop i} |- prop i by LTLAXIO1:42;
thus not {prop i} |-0 'G' prop i by th266,th21cp;
end;
*